1996
DOI: 10.1074/jbc.271.40.25027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Truncated Forms of the KdpD Protein, the Sensor Kinase of the K+-translocating Kdp System of Escherichia coli

Abstract: The expression of the kdpFABC operon, coding for the K+-translocating Kdp system, is controlled by the two regulatory proteins, KdpD and KdpE, which belong to the group of sensor kinase/response regulator systems. This study describes the construction and analysis of KdpD sensor kinases, in which different deletions in the N-terminal part of the protein were introduced. Truncated KdpD proteins, in which the membrane-spanning segments were deleted, had lost their phosphorylation capacity. Truncated KdpD protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 37 publications
3
47
1
1
Order By: Relevance
“…This presumption is supported by the differentiated response of KdpD proteins with individual substitutions of Arg residues toward K ϩ limitation and osmotic upshock (9). Compared with other known sensor kinases, KdpD is the only protein that has a large, hydrophilic N-terminal domain of about 400 amino acids in length (17,18) (Fig. 1) that this domain is more conserved then other regions of KdpD.…”
Section: ) (3)mentioning
confidence: 59%
“…This presumption is supported by the differentiated response of KdpD proteins with individual substitutions of Arg residues toward K ϩ limitation and osmotic upshock (9). Compared with other known sensor kinases, KdpD is the only protein that has a large, hydrophilic N-terminal domain of about 400 amino acids in length (17,18) (Fig. 1) that this domain is more conserved then other regions of KdpD.…”
Section: ) (3)mentioning
confidence: 59%
“…Signal transduction mediated by truncated forms of KdpD was previously tested in E. coli deleted for other K ϩ uptake systems (TrkG and TrkH) leaving Kdp as the main K ϩ transport system. Because of the importance of the Kdp system as the major K ϩ uptake system, kdpFABC expression was never completely blocked (17). Therefore, we tested the transcriptional induction of kdpFABC with E. coli HAK006 (11) that synthesizes the constitutive K ϩ uptake systems, TrkH, TrkG, and Kup.…”
Section: Kinase and Phosphotransfer Activities And The Influence Of Nmentioning
confidence: 99%
“…The influence of the N-terminal truncations in KdpD on the transcriptional regulation of kdpFABC was tested in a trk Ϫ background. It was shown that the truncation of amino acids 12-128 influences the level of kdpFABC expression, whereas the truncation of amino acids 128 -391 exhibits expression levels that were comparable with wild-type KdpD (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Before use, 10His-KdpE was dialyzed against buffer E without KCl and imidazole. Alternatively, KdpE was purified following a method described before (12).…”
Section: Materials-[␥-mentioning
confidence: 99%